Air Pollution and Serum Glucose Levels. Issue 27 (July 2015) - Sade, Maayan Yitshak; Kloog, Itai; Liberty, Idit F.; Katra, Itzhak; Novack, Lena; Novack, Victor; Leischik., Roman
<x xml:space="preserve">Abstract</x> Abstract Recent studies demonstrated an adverse effect of chronic exposure to air pollution (AP) on metabolic syndrome and its components. In a population-based study, we investigated the association between exposure to ambient AP and serum glucose (SG), among subjects with normal glucose, impaired fasting glucose (IFG), and diabetes mellitus (DM). We included 1, 063, 887 SG tests performed in 131, 882 subjects (years 2001–2012). Exposure data included daily levels of SO2, NO2 and other pollutants of industrial, traffic, and nonanthropogenic sources. Demographical, clinical, and medications purchase data were assessed. Log-transformed SG levels were analyzed by linear mixed models adjusted for seasonal variables and personal characteristics. SG increases (%increase [95% CI]), among subjects with normal glucose, IFG, and DM, respectively, were associated with 6.36 ppb increase of NO2 measured 24 to 72 hours before the test (0.40% [0.31%; 0.50%], 0.56% [0.40%; 0.71%], and 1.08% [0.86%; 1.29%]); and with 1.17 ppb increase of SO2 measured 24 hours before the test (0.29% [0.22%; 0.36%], 0.20% [0.10%; 0.31%], and 0.33% [0.14%; 0.52%]). Among DM population, weakest association was observed among patients treated with Metformin (0.56% increase in SG [0.18%; 0.95%]). In conclusion, NO2 and SO2 exposure is associated with small but significantly increased levels of SG. Although DM patients were found to be more susceptible to the AP induced SG variations, Metformin treatment seem to have a protective effect. Given the chronic lifetime exposure to AP and the broad coverage of the population, even small associations such as those found in our study can be associated with detrimental health effects and may have profound public health implications.